Baby Incubator with Room Temperature and Skin Temperature Monitoring Via IoT-Based WIFI Network - Mahendra, Farhel Gading; Rahmawati, Triana; Kholiq, Abdul; Farooq Mujahid, Muhammad Umer (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
Newborns require special attention to the labor process, this affects the health of the baby itself. Similarly, with premature babies who have a high level of sensitivity to the surrounding environment, one of the biggest causes of death in premature babies is hypothermia, therefore adjustments are needed starting from room temperature and skin in the baby incubator. The purpose of this study is to develop a monitoring system that will facilitate the performance of nurses in monitoring the parameters of the baby incubator. Related to this, an incubator device is needed that can be monitored remotely. This module uses a wifi network system for data transmission. Using the ESP32 module assembled into a module for monitoring and control which will then be displayed on the LCD and in the blynk as a monitoring display. Data transmission will be communicated using an external WIFI network and the monitoring results of each sensor will be displayed on Blynk. The highest error values were 1.24% for incubator room temperature parameters and 1.15% for skin temperature parameters. The results showed that there were still inaccuracies in some parameter readings, one of the factors that read inaccurate parameters was sensor sensitivity. This research is expected to help medical personnel to facilitate monitoring the condition of premature babies in baby incubators.